INFECTIOUS EXANTHEMA IN CHILDREN - E. O. Utenkova (LLC "Diagnostics and Vaccines", 2018)
The article considers the main childhood infections that occur with the exanthema. Rules for the description of exanthemа, their classification, basic differential-diagnostic symptoms are presented. The article is illustrated with photographs of their author's archive.